Development and performance evaluation of an ultralow flow nanoliquid chromatography‐tandem mass spectrometry set‐up. Issue 17 (14th July 2014) - Köcher, Thomas; Pichler, Peter; De Pra, Mauro; Rieux, Laurent; Swart, Remco; Mechtler, Karl; Zahedi, René P.; Ueffing, Marius; Sickmann, Albert
<x xml:space="preserve">Abstract</x> LC‐MS/MS is the most commonly used technique for the identification and characterization of proteins. The efficiency of the electrospray process is a critical factor in LC‐MS/MS. Despite the benefits associated with very low flow rates for the ionization efficiency, most LC‐MS/MS platforms are operated at relatively high flow rates. The purpose of this work was to develop a nano LC system operable at a flow rate of 20 nL/min, applicable for routine analysis in proteomics laboratories. Peptide separation was performed with an analytical column packed with 2 μm porous chromatographic beads, a length of 25 cm and an inner diameter (i.d.) of 25 μm. Practical usability, reproducibility, and overall performance of the system were evaluated with a tryptic peptide mixture generated from HeLa cells. Using 100 ng of sample, we identified on average 3721 protein groups based on 25, 699 peptides. We demonstrate that the number of peptides identified with this system increases with decreasing flow rates. Probing the sensitivity of the set‐up we analyzed only 10 ng of the sample, identifying an average number of 2042 protein groups based on 11 424 peptides. All MS data have been deposited in the ProteomeXchange with identifier PXD000396 (http://proteomecentral.proteomexchange.org/dataset/PXD000396).